Construindo lealdade online: a renda do consumidor faz diferença? - Rocha, Viviane Moura (2015)
Ecommerce sales volume is growing very fast. The challenge retailers’ face to develop customer loyalty in their online operations is even tougher than in offline stores. In Brazil, the drivers of e-tail growth are mainly related to the expansion of the access into ecommerce of low-income consumers segment, better known as Class C. However, little is known about the behavior of this segment in online retail. This research aims to evaluate the e-Loyalty phenomenon analyzing Brazilian consumers from both income segments (upper and lower), in two stages: exploratory and quantitative. In the exploratory phase, 16 consumers were interviewed and a content analysis was done. In the quantitative stage, data were collected via web survey from 1,020 consumers and were analyzed with the use of structural equation. The research was guided by the 'e-Loyalty Classic Model', identified through the literature review. This model considers e-loyalty as a function of e-Quality, e-Satisfaction and e-Trust. This research aims to evaluate these relationships in the Brazilian market, with consumers from different income levels. This goal was motivated by the growing share of lower income consumers in the Brazilian ecommerce, and from some evidences that theirs behavior in ecommerce could be different from upper income segment. Among the main results, it was found that consumers from upper-income give more weight to the quality of website information, while consumers in the lower income emphasize the importance of fulfillment. For both segments, upper income consumers and lower income consumers, e-Satisfaction is more important than e-Trust to determine e-Loyalty. The importance of e-Satisfacion is even more important in lower income consumers. Such differences attested the moderation of the income variable in defining relations of e-Loyalty, and contributed to a better understanding of the loyalty phenomenon.